OPTIMIZATION OF HARDENING AISI 1045 AS MATERIAL FOR CANE CUTTER BLADES USING THE TAGUCHI METHOD - Gunawan, Indra; Putri, Fenoria; Witjahjo, Soegeng; Mushafiqih, Harry (AUSTENIT, 2022)
PT. X is a company that manufactures sugar. The situation of firm X cannot be described as ideal due to the need for extensive study, particularly on the cane cutter's blade. A common indication of cane cutters is a rapid rate of wear. In this study, researchers employed a qualitative technique based on the taguchi method. The taguchi approach is a modern engineering technique that strives to improve the quality of products and processes while reducing costs and maximizing resources. The taguchi experimental strategy is more effective because it permits research incorporating a large number of variables and numbers. Since a larger hardness response is preferable, the largest confirmation value is the ideal parameter value for the knife manufacturing process on the cane cutter. When measuring the hardness of the blade material on a cane cutter, temperature is a highly important component. According to the findings of the hardness test, the hardest material at a temperature of 750oC and a cooling medium of NaCl solution with a hardness value of 12.4 HRC is, and the hardest material at a temperature of 800oC and a cooling medium of NaOH solution with a hardness value of 59.7 HRC is.